Issues in procurement methods in public organizations: A case of Tanzania Aviation Authority (TAA) - Kheri, Ashura Chimbeni (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Award of the Degree of Master of Science in Accounting and Finance (MSc-A&F) of Mzumbe University Dar es Salaam Campus College